Help the village through a human resource development program in Grinting Village, Bulakamba District, Brebes Regency - Halim Purnomo; Aris Slamet Widodo; Gatot Supangkat Samidjo; Nano Prawoto; Ahmad Hermawan (Peneliti Teknologi Teknik Indonesia, 2022)
Human resources that have competitiveness are the main component in managing the people of Grinting Village, Bulakmba District, Brebes Regency, Central Java, to be able to compete in the era of globalization as it is today. This community service activity aims to produce superior human resources in Grinting Village so that they are able and independent in managing existing produce and culture to become a source of community independence. This community service activity program is carried out involving the community to develop various community capabilities in managing villages towards Grinting which are able to adapt to changing times in accordance with the acceleration of information technology as it is today. Various community activities have been carried out which were initiated by the University of Muhammadiyah Yogyakarta together with the jam'iyyah driving community held training and assistance in moving the potential components in Grinting Village such as assisting in managing Islamic shia and developing the local community's economy. This community service activity is able to encourage the community to develop the ability to manage the potentials of Grinting Village.